Presentation - Mauad, Frederico Fábio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The Hydrometry Group is part of the Center for Water Resources and Environmental Studies - CRHEA, located in the municipality of Itirapina-SP, near the Lobo reservoir (Broa), 25 km away from campus 1 of USP in São Carlos, SP. CRHEA belongs to the School of Engineering of São Carlos and provides the infrastructure for the postgraduate program in Environmental Engineering Sciences.